2021
DOI: 10.23887/jisd.v5i4.36693
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Television Shows that are of Favored by Elementary School Students

Abstract: The various television shows can now be easily accessed by children for 24 hours without the need for parental controls. Television shows that are presented are of various types, ranging from educational shows, cartoons to soap operas. This article aims to map out television shows that are of favored by elementary school students. The approach of this research is qualitative descriptive. The subjects of this study were elementary school students from grade I to grade VI. The data of this study were collected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Researchers tried to observe several days of conducting interviews with teachers regarding the impact of watching the episodes of the animated series Adit & Sopo Jarwo that were broadcast (Annisya & Baadilla, 2022;Habsari, 2020;Rahmawati & Muhroji, 2022). It turned out to have a positive impact, namely that students became more active in group activities and adopted a mutual cooperation attitude in school activities and became more independent when complete assignments and homework (Baharun & Ummah, 2020;Sabardila et al, 2021;Umah et al, 2022). Based on these results, it can be explained that the animated series Adit & Sopo Jarwo contains educational values of cooperative characters, especially in the episode "Serunya Kerja Bakti dan Tamasya Bersama" and independent characters, especially in the episode "Bunda Pergi Adel Mandiri", so that the animated series can be used as an alternative medium for teachers in instilling the values of these characters in their children for elementary school age students, the character of mutual cooperation and caring can be instilled from an early age so that they become human beings with character based on Pancasila (Faiz & Faridah, 2022;Sabardila et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers tried to observe several days of conducting interviews with teachers regarding the impact of watching the episodes of the animated series Adit & Sopo Jarwo that were broadcast (Annisya & Baadilla, 2022;Habsari, 2020;Rahmawati & Muhroji, 2022). It turned out to have a positive impact, namely that students became more active in group activities and adopted a mutual cooperation attitude in school activities and became more independent when complete assignments and homework (Baharun & Ummah, 2020;Sabardila et al, 2021;Umah et al, 2022). Based on these results, it can be explained that the animated series Adit & Sopo Jarwo contains educational values of cooperative characters, especially in the episode "Serunya Kerja Bakti dan Tamasya Bersama" and independent characters, especially in the episode "Bunda Pergi Adel Mandiri", so that the animated series can be used as an alternative medium for teachers in instilling the values of these characters in their children for elementary school age students, the character of mutual cooperation and caring can be instilled from an early age so that they become human beings with character based on Pancasila (Faiz & Faridah, 2022;Sabardila et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies about character education in Indonesian elementary school have carried out. Studies related to programs that are of interest to children have character education values [16]. Studies related other showed that the use of the cartoon "Cloud Bread" can be used as a suitable medium to instill character education in children which includes: respecting parents, respecting friends and other people, loyal friends, cooperation, motivating each other, gentle, diligent, not easily discouraged, enthusiastic, problem-solving, creativity, and mutual love between families [17].…”
Section: Introductionmentioning
confidence: 99%
“…The immediate home environment plays a pivotal role in shaping toddlers' media exposure, with parents, extended family, and caregivers providing essential stimulation and introducing them to television content (Hariyanto, 2018;Sabardila et al, 2021;Sanityastuti et al, 2015). Parents are instrumental in preventing children from imitating negative scenes from television shows (Ginting & Pratiwi, 2017).…”
Section: Introductionmentioning
confidence: 99%